Detection of hepatitis B virus infection in German blood donors 2008–2015. Issue 3 (5th February 2020) - Scheiblauer, Heinrich; Heiden, Margarethe; Funk, Markus; Oberle, Doris; Kreß, Julia; Jork, Christine; Chudy, Michael
Abstract : Background and objectives: Assessment of HBV‐NAT testing compared to HBsAg and anti‐HBc screening in German blood establishments for the period 2008–2015. Materials and methods: Blood donations screened for HBsAg and anti‐HBc along with HBV‐NAT were evaluated. Sensitivity of HBsAg and HBV‐NAT tests was compared in 30 HBV seroconversion panels and with the viral load of the NAT‐only cases. Residual risk for HBV in the WP was modelled. Results: A total of 45 270 111 donations were evaluated. There were 29 NAT‐only cases in the HBsAg‐negative HBV‐WP, one by ID‐NAT and 28 by MP‐NAT. MP‐NAT, on average, showed higher sensitivity than HBsAg testing: MP‐NAT‐LoD of 146 IU/ml vs. 362 IU/ml HBV DNA for positive HBsAg detection (range 135–1502 IU/ml), resulting in 3·1 days (range 2·0–4·8 days) earlier HBV detection. Viral loads of the NAT‐only cases confirmed the sensitivity of the HBV tests in the seroconversion study. One HBsAg‐negative case was due to a new HBsAg mutant combination. There was one HBsAg‐reactive only case. In addition, HBV incidence in the HBV‐WP included 41 HBsAg‐/HBV‐NAT‐positives and three HBV transmission cases. The residual risk for HBsAg was estimated to be 1:1 619 419–1 268 474 compared to 1:2 793 365–2 134 702 for MP‐NAT. Within chronic HBV (HBsAg‐/anti‐HBc‐positive and MP‐NAT‐negative) 70% were ID‐NAT positive at low viral load (median 20 IU/ml). Among anti‐HBc‐only, supplementary ID‐NAT detected 23 occult HBV infections. Conclusions: In the HBV‐WP, MP‐NAT provided a higher sensitivity than HBsAg testing, obtained a considerably higher yield and reduced the risk for HBV transmission. In later HBV stages, anti‐HBc screening and HBV‐ID‐NAT intercepted potentially infectious donations.